2008
DOI: 10.1159/000121853
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Clustering and Seasonality in Diagnosing Skin Cancers in Wallonia (South-East Belgium)

Abstract: Background: In Westernized populations, the number of diagnosed cases of primary cutaneous cancers, particularly malignant melanomas and basal cell carcinomas (BCC), has been previously shown to fluctuate during specific periods of the year. Objective and Method: The aim of the present 6-year study was to explore the seasonality if any in skin cancer detection in Wallonia (south-east Belgium). Results: For both malignant melanomas and BCC late spring/early summer and mid-autumn were the periods of highest diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…Moreover, a clinically based study conducted in Wallonia also found a higher number of cases diagnosed in late spring/early summer [32]. While we found no difference according to age and sex, previous reports suggested that seasonality was more pronounced among females [5,18,29,33] and people over 55 years of age [5,6,12].…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, a clinically based study conducted in Wallonia also found a higher number of cases diagnosed in late spring/early summer [32]. While we found no difference according to age and sex, previous reports suggested that seasonality was more pronounced among females [5,18,29,33] and people over 55 years of age [5,6,12].…”
Section: Discussioncontrasting
confidence: 53%
“…The results of the current study are consistent with previous studies showing a higher number of searches during the summer (30,39). This could be due to the fact that diagnoses of NMSC and melanoma are more common in the late spring and early summer (49), which could influence an increase in search volume. In addition to these factors, search volume might be influenced by public health policies and media campaigns (50).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Figure 2 demonstrates that the public interest increases in late spring, when people more frequently wear short-sleeved clothing due to rising temperatures and decreases in late summer when temperatures begin to decrease in Germany [ 36 ]. The seasonal variation may also be affected by diagnoses of NMSC and melanoma, which are reported to be significantly higher in late spring and early summer [ 37 , 38 ]. These seasonal differences in search volume were also reported by Bloom et al with regard to skin cancer and melanoma in the United States [ 17 ].…”
Section: Discussionmentioning
confidence: 99%